Effects of Recurring IPC vs. rIPC Maneuvers on Exercise Performance, Pulse Wave Velocity, and Red Blood Cell Deformability: Special Consideration of Reflow Varieties - Marijke Grau; Benedikt Seeger; Lukas Mozigemba; Roland Roth; Luca Baumgartner; Hans-Georg Predel; Wilhelm Bloch; Fabian Tomschi (Biology, 2022)
Beneficial effects of (remote) ischemia preconditioning ((r)IPC), short episodes of blood occlusion and reperfusion, are well-characterized, but there is no consensus regarding the effectiveness of (r)IPC on exercise performance. Additionally, direct comparisons of IPC and rIPC but also differences between reflow modes, low reflow (LR) and high reflow (HR) in particular, are lacking, which were thus the aims of this study. Thirty healthy males conducted a performance test before and after five consecutive days with either IPC or rIPC maneuvers (n = 15 per group). This procedure was repeated after a two-week wash-out phase to test for both reflow conditions in random order. Results revealed improved exercise parameters in the IPC LR and to a lesser extent in the rIPC LR intervention. RBC deformability increased during both rIPC LR and IPC LR, respectively. Pulse wave velocity (PWV) and blood pressures remained unaltered. In general, deformability and PWV positively correlated with performance parameters. In conclusion, occlusion of small areas seems insufficient to affect large remote muscle groups. The reflow condition might influence the effectiveness of the (r)IPC intervention, which might in part explain the inconsistent findings of previous investigations. Future studies should now focus on the underlying mechanisms to explain this finding.